The enzymatic synthesis of EPA-rich medium- and long-chain triacylglycerol improves the digestion behavior of MCFA and EPA: evidence on in vitro digestion. Issue 1 (6th December 2021) - Wang, Yandan; Cao, Minjie; Liu, Ruijie; Chang, Ming; Wei, Wei; Jin, Qingzhe; Wang, Xingguo
Abstract : EPA-rich medium- and long-chain triacylglycerol was synthesized from MCT and EPA-rich fish oil by transesterification. The fate of different oils across the gastrointestinal tract was subsequently simulated using an in vitro digestion model. Abstract : Medium-chain triglyceride (MCT) and eicosapentaenoic acid (EPA) have been widely applied in nutritional supplementation. However, when administered individually or mixed, they were unable to maximize their nutritional value. Hence, EPA-rich medium- and long-chain triacylglycerol (MLCT) was synthesized from MCT and EPA-rich fish oil (FO) by enzymatic transesterification. The fatty acids in triglyceride (TAG) were rearranged which resulted in significant changes in TAG profiles compared to the physical mixture of MCT and FO (PM). EPA-containing MML (MML, MLM and LMM) and LLM (LLM, LML and MLL) type TAGs account for 70.21%. The fate of different oils (MCT, FO, PM, and MLCT) across the gastrointestinal tract was subsequently simulated using an in vitro digestion model. The results showed that the physical and structural characteristics of different oils during digestion depended upon the oil type and the microenvironment they were in. After 120 min of small intestine digestion, the degree of hydrolysis for MLCT was higher than that for the other three oils. The final FFA release level was in the following order: MLCT (102.79%) > MCT (95.20%) > PM (85.81%) > FO (74.18%). This can be attributed to the composition and positional distribution of fatty acids in TAGs. What's more, LCFAs (EPA) in MLCT mainly existed in the form of sn -2 MAG, which was conducive to their subsequent absorption and transport. These results may aid in the future rational design of structural lipids, thereby regulating lipid digestion and maximizing the nutritional value of oils.